SIMS relative sensitivity factors for Al/Mg in synthetic and Madagascar hibonite - MacPherson, Glenn J.; Beckett, J.; Kita, N. T.; Nagashima, K.; Krot, A. N.; Fournelle, J.; Kööp, L.; Hertwig, Andreas; Rose, T. R.; Davis, A. M. (Chemical geology, 2023)
We synthesized three compositions of hibonite, differing in their levels of MgO and TiO2 that were chosen to cover most of the range of compositions of natural meteoritic hibonite. The goal was to evaluate the appropriateness of the use of terrestrial Madagascar hibonite as a standard in the SIMS analysis of initial 26Al/27Al ratios in calcium‑aluminum-rich inclusions, and especially its use for the determination of the 27Al/24Mg relative sensitivity factor (RSF). Concern exists because of the high levels of FeO and rare earth elements (REE) in the terrestrial mineral relative to meteoritic samples. Our results show that, provided the specific Madagascar hibonite samples in a given lab are carefully characterized in terms of mineral chemistry (including Fe, Th, and REE) via electron microprobe analysis, the terrestrial mineral gives RSFs that are within 2% of those determined for the synthetic samples. The 27Al/24Mg SIMS/EPMA RSF based on the synthetic hibonite compositions alone is 0.779 ± 0.003; combining all synthetic and Madagascar hibonite analyses yields a RSF of 0.777 ± 0.003. We cannot rule out that RSFs might be somewhat different using different SIMS instruments, or among individual SIMS sessions, so RSFs should be evaluated for each SIMS session.
Online verfügbar: 16. Dezember 2022, Artikelversion: 28. Dezember 2022
Gesehen am 20.06.2023